(untitled) (Experimental biology, 2016)
The study presents the date of effects of atmospheric pressure low-temperature plasma generated by dielectric barrier discharge on viability and morphological features of DU145 human metastatic prostate cancer cells. The effect of low temperature plasma on cells depends on the dose and exposure time. If lower doses of plasma cause cell proliferation, the highest doses couse death of cancer cells. Thus, in relatively high dose of plasma, i.e. plasma dose №7 (frequency - 250 Hz, power - 2.2 W, and time of exposure - 30 seconds) after 24 and 48 hours post 1 minute incubation of cells with plasma treated saline solution reduced cell viability 47 and 38%, respectively, and in post 10 minutes incubation of cells reduces cell viability 19% and 11%. These results demonstrate the potential clinical use of the proposed method for the treatment of prostate cancer.